Nietzsche's Dancers Isadora Duncan, Martha Graham, and the Revaluation of Christian Values - LaMothe, K. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
This book investigates the role Nietzsche's dance images play in his project of "revaluing all values" alongside the religious rhetoric and subject matter evident in the work of Isadora Duncan and Martha Graham, who found justification and guidance in Nietzsche's texts for developing dance as a medium of religious expression.